Hubungan Penggunaan Model Pembelajaran Kooperatif Tipe Group Investigation ( GI ) terhadap Hasil Belajar PKn Siswa Kelas V SD Inpres Minasaupa 1 Kecamatan Rappocini Kota Makassar - Jumiati Nur; Andi Sugiati (JED (Jurnal Etika Demokrasi), 2017)
This research is experimental research by using one class as research sample that is class V with total student 40 peoples. This study aims to determine the relationship between the use of Cooperative Learning Model Type Group Investigation (GI) In Students Class V SD Inpres Minasa Upa 1 with reference to the completeness of learning outcomes, increased student activity of six observed aspects, good teacher activity on the implementation of cooperative learning type Group Investigation (GI). The result of the research shows that: The relationship between the use of cooperative learning model of Group Investigation type and the result of the students' learning in the know from the hypothesis test with the product moment with the result of r = 0.9111 is categorized "very high" and t test with result t = 0,9111 both t = 0.320 (significant 5%) and t = 0.413 (significant 1%). The results of these calculations can prove alternative hypothesis to give positive results / alternative hypothesis can be accepted, namely The existence of the relationship between cooperative learning model Group Investigation type with student learning outcomes. Based on the result of the research, there is a Cooperative Learning Group Type Investigation (GI) relationship with the learning outcomes of Civics in grade V SD Inpres Minasa Upa 1 Kec. Rappocini city of Makassar.Keywords: Learning Outcomes, Group Investigation (GI), Student.